Analisis Penerapan Tax Planning Atas Pajak Penghasilan Pasal 21 Pada Perum Bulog Sub Divre Pekalongan - Pramesti, Revona Cahya; Noermansyah, Asrofi Langgeng; Aryanto (Journal of Public and Business Accounting, 2020)
Abstract. Tax Planning is one of function from Tax Management that is used for estimating the amount of paid taxes and other things to avoid taxes. Meanwhile, income tax 21’s article is income taxes such as salary, wages, honorarium, allowances, and other payments in name of anything related to work or position, services, and personal activity. This research was for knowing the practice of tax planning on income tax 21’s article at Perum BULOG Sub-Divre Pekalongan. The technique used in collecting data are observation, interviews, documentation and literature. The method used in analysing data was Descriptive Quantitative and Qualitative Method. Result of this research shows that Gross Up Method was the most proper method for calculating Income Tax 21’s article, because based on subvention of income taxes clause for employee include of reduced cost so that company profits become smaller and so owed taxes either. Keywords: Tax Planning, Income Taxes article 21